Distribution of GFAP in Squamata: Extended Immunonegative Areas, Astrocytes, High Diversity, and Their Bearing on Evolution - Lõrincz, Dávid; Kálmán, Mihály (Frontiers in Neuroanatomy, 2020)
Squamata is one of the richest and most diverse extant groups. The present study investigates the GFAP-immunopositive elements of 5 lizards and 3 snake species; each represents different family. The study continues our former studies on birds, turtle and caiman brains. Although several studies have been published on lizards, they usually only investigated one species. Almost no data is available on snakes. The animals were transcardially perfused. Immunoperoxidase reactions were performed with a mouse monoclonal anti-GFAP (Novocastra). The original radial ependymoglia is enmeshed by secondary, non-radial processes almost beyond recognition in several brain areas like in other reptiles. Astrocytes occur but only as complementary elements like in caiman but dislike from turtles, where astrocytes are absent. In most species, extended areas are free of GFAP – a meaningful difference from other reptiles. The predominance of astrocytes and the presence of areas free of GFAP immunopositivity are characteristic of birds and mammals, therefore they must be apomorphic features of Squamata, which appeared independently from the evolution of avian glia. However, these features show a high diversity; in some lizards they are even absent. There was no principal difference between the glial structures of snakes and lizards. In conclusion, the glial structure of Squamata seems to be the most apomorphic one among reptiles. The high diversity suggests that their evolution is still intense. The comparison of identical brain areas with different GFAP content in different species may promote understanding the role of GFAP in the neuronal networks. Our findings are in accordance with the supposal based on our previous studies that the GFAP-free areas expand during evolution.